Kolaborasi Akademisi Dan Sekolah Dalam Meningkatkan Keterampilan Coding Siswa Di SD Negeri 126 Rejang Lebong - Martiani Martiani; Azizatul Banat; Aziiz Rahman Putra; Mariska Febrianti; Dwi Ratna Sari (Universitas Dehasen Bengkulu, 2026)
The development of digital technology requires students to master logical thinking and problem-solving skills from an early age. At SD Negeri 126 Rejang Lebong, observations show students' enthusiasm for high-tech learning, but their coding skills are still low due to limitations in teacher competence and learning media. This PKM program aims to improve students' coding and computational thinking skills through interactive, practice-based learning, involving 21 fifth-grade students, 1 accompanying teacher, 4 lecturers, and 2 physical education students. The approach of the activity is in line with Piaget's constructivism theory, experiential learning, and Wing (2006), which emphasizes the importance of computational thinking to train logical, systematic, and efficient thinking in problem solving. Activities include presentations, demonstrations, and simple coding practices directly, which enhance students' creativity, logical thinking, and problem-solving skills, while strengthening teachers' capacity. The results showed positive responses from students and teachers, as well as the potential for sustainable implementation in schools. Thus, this PKM presents a contextual, enjoyable coding learning model that supports the continuous development of students' abilities.